Precarious autonomies: an analysis of technologies for people with intellectual disabilities - Moyà-Köhler, Joan; Domènech, Miquel (Teknokultura. Revista de Cultura Digital y Movimientos Sociales, 2021)
Digital technologies have burst into the lives of people with disabilities with the promise of offering more autonomy and accessibility with remarkable achievements in some areas. Learning disability, however, has been a field in which such developments have been more modest and still presents certain uncertainties. The issue of autonomy, in particular, poses problems in its implementation, especially when it is considered from the point of view of an autonomous individual subject capable of making independent decisions. Through an ethnographic study carried out in an independent living service in Catalonia, we analyzed two cases of technology implemented to facilitate the autonomy of people with learning disabilities. From the comparison between the two cases, we have shown how the final outcome of the experiences has much to do with the interactions between the different conceptions of autonomy that are present and the way in which the role of technology in achieving independent living is conceived. The study identifies that thinking about the whole network of relationships that is established as a set of precarious balances is critical to dealing with complex matters such as the right to decide, the autonomy or non-invasive support in the daily life of people with learning disabilities.